A dynamic MST-deltaCoVaR model of systemic risk in the European insurance sector - Anna Denkowska; Stanisław Wanat (Statistics in Transition New Series, 2021)
This work is a response to the EIOPA paper entitled "Systemic risk and macroprudential policy in insurance", which asserts that in order to evaluate the potential systemic risk (SR), the build-up of risk, especially risk arising over time, should be taken into account, as well as the interlinkages occurring in the financial sector and the whole economy. The topological indices of minimum spanning trees (MST) and the deltaCoVaR measure are the main tools used to analyse the systemic risk dynamics in the European insurance sector in the years 2005-2019. The article analyses the contribution of each of the 28 largest European insurance companies, including those appearing on the G-SIIs list, to systemic risk. Moreover, the paper aims to determine whether the most important contribution to systemic risk is made by companies with the highest betweenness centrality or the highest degree in the obtained MST.
Keywords: 519; systemic risk; minimum spanning trees; deltaCoVaR; insurance sector